Kajian Kualitas Pelayanan dan Loyalitas Nasabah Perbankan di Indonesia - Dedy Ansari Harahap; Dita Amanah (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2019)
The purpose of this study is to examine the relationship of service quality and loyalty of banking customers in Indonesia. Banking as an institution of financial institutions that have a big role for the economy that can prosper the community. Customers who are part of the public interest in transacting products in the form of services marketed by banks in Indonesia. The quality of services provided by a bank will have an impact on customer loyalty. This research method compares the results of research and journals that examines the loyalty of banking customers in Indonesia. Then reviewed and reviewed theories of service loyalty that has been there so it can be concluded the customer's consideration of transactions in a bank. The findings from previous studies show that the dimensions of service quality affect the loyalty of Indonesian banking customers. This can be seen in several banks spread over Indonesia regarding the quality of service and customer loyalty. The results of the study of some previous research, can be a reference and consideration for banks and stakeholders in hooking and retaining customers to remain loyal to use his services in transactions at a bank